Modes of occurrence of highly-elevated trace elements in superhigh-organic-sulfur coals. (15th September 2015) - Liu, Jingjing; Yang, Zong; Yan, Xiaoyun; Ji, Dongping; Yang, Yongchang; Hu, Luchang
Highlights: The Guiding and Heshan coals are characterized by superhigh-organic-sulfur (SHOS). The SHOS coals have highly-elevated concentrations of V, Cr, Se, Mo, Cd, Re, and U. V, Cr, Se, Re, U, and Mo in these SHOS coals are mainly associated with organic matter. Cadmium is mainly distributed in sulfide minerals. A proportion of Re is associated carbonate fraction. Abstract: The concentrations and modes of occurrence of highly-elevated trace elements including V, Cr, Se, Mo, Cd, Re, and U in some late Permian coals preserved within marine carbonate successions from Southwest China, were investigated using inductively coupled-plasma mass spectrometry (ICP-MS), sequential chemical extraction procedures (SCEP), field emission-scanning electron microscopy in conjunction with an energy-dispersive X-ray spectrometer (FE SEM–EDS), and X-ray powder diffraction analysis (XRD). The coals present in this study are characterized by superhigh-organic-sulfur, ranging from 5.01% to 9.87%, and by highly-elevated concentrations of V (859 ppm on average), Cr (370 ppm), Se (29.3 ppm), Mo (364 ppm), Cd (3.87 ppm), Re (0.47 ppm), and U (214 ppm). The minerals in the coals are predominantly composed of illite or mixed-layer illite/smectite, which, together with quartz, were derived from sediment-source region. The SCEP results showed that elements V, Cr, Se, Re, U, and Mo are mainly associated with organic matter of the coal, and to a lesser extent, are associated with illite or mixed-layer illite/smectite. Traces of U-bearing minerals (coffinite and brannerite) were identified in the coal. Cadmium is mainly and Cr and Mo are partially distributed in sulfide minerals. A significant proportion of Re is also associated with the carbonate fraction.